(untitled) (Research, Society and Development, 2020)
With the objective to evaluate the effect of nitrogen levels (0, 60, 120, 180 and 240 kg of N ha-1) on green dry matter (GDM) yield and morphogenetic and structural characteristics and nitrogen nutrition index (NNI) of Brachiaria ruziziensis, was carried out an experiment under field conditions in Roraima´s savannas. Nitrogen fertilization increased significantly (P<0.05) DM yields, number of tillers, number of leaves/plant, medium blade length, leaf area, leaf senescence rate, leaf appearance and elongation rates. Maximum GDM yields, leaf elongation rates, leaf length and number of leaves/plant were obtained with the application of 220.6; 238.6; 191.5 and 225.5 kg of N ha-1, respectively. The critical level of N was reduced with increased grass forage yield. The NNI, for all levels of N evaluated, was insufficient to supply the critical level of N of the grass. The NNI, efficiency of utilization and apparent N recovery were inversely proportional to the increased N levels.